Quantitative analysis of insulator degradation in a single layer solenoid by renormalization of the transmission parameter - Kim, Kwangho; Han, Junhee; Chai, Jangbom; Nah, Wansoo (Electronics (Switzerland), 2020)
In this paper, a novel method to quantitatively analyze insulator degradation in a single layer solenoid is proposed. The suggested method employs renormalization of scattering parameters to efficiently detect changes of permittivity in a degraded solenoid. Firstly, a transmission line model, including a locally degraded part in the insulator, was developed, and it was determined that the phase information of the transmission parameter was very informative to check the permittivity change in the transmission line. To check the workability of this idea in a solenoid, a 30-turn single-layer solenoid was designed and fabricated, and 51 degraded states for mimicking insulation deterioration in each turn were introduced by installing additional insulator rings, which increased local relative permittivity. The phase data of the measured transmission parameter turned out to be useful for quantifying changes of the insulator in the solenoid. To maximize the detectability, the measured scattering parameters were renormalized with different reference impedances, which was very useful for detecting degradation in the transmission parameter. In this paper, detailed procedures for quantitatively analyzing degradation of an insulator are proposed and we verify that the suggested renormalization technique is very promising for effectively evaluating the degradation of a solenoid.
Keywords: Diagnostic method; Scattering parameter renormalization; Single layer solenoid; Transmission line theory